Anthropization Affects the Assembly of Bat-Bat Fly Interaction Networks - Ramalho, Daniel F.; Diniz, Ugo M.; Aguiar, Ludmilla M. S. (Frontiers in Environmental Science, 2021)
Increasing anthropization is detrimental to the natural environment and the quality of life, affecting populations, communities, and the relationships between organisms. One of the most unique relationships in the animal world is parasitism, which often involves tightly specialized interactions between pairs of species. Bat flies, for example, are obligate ectoparasites represented by two highly adapted dipteran families that usually parasite a single bat species or genus. Recent studies have shown that bat flies could carry pathogens such as bacteria and viruses, transmitting them among bat individuals in a colony. Because host roost characteristics can influence bat-fly parasitism, we aimed to assess whether the ecological networks between parasites and their host bats are influenced by the degree of habitat anthropization. Our hypothesis was that bat-fly interaction networks would be less specialized and more nested in highly anthropized sites. We collected bat fly individuals from bats captured at 21 sampling sites located in the Federal District of Brazil and quantified the amount of natural and anthropized area within a 3-km buffer from the sampling site. Areas consisting of agriculture, construction, mining, roads, or any man-made structure were considered anthropized. Sites presented different degrees of anthropization, with areas ranging from 100% anthropized to areas retaining full natural cover. We built bat-bat fly networks for each of the sites and excluded those with less than 70% of sampling completeness. We calculated key weighted structural metrics for each network, such as nestedness, specialization, and modularity. The effect of the reduction in natural cover on structural metrics was assessed through GLMMs, controlling for network size and ectoparasite diversity. Nestedness increased with the amount of anthropization while specialization decreased. The two metrics showed a strong negative correlation with one-another. Modularity did not change and was overall high in all networks. This result suggests that anthropization may influence the assembly of bat-bat fly networks, leading to the emergence of a hierarchical assembly of interactions as parasites become less specialized and interact with a wider variety of hosts. Less specialized relationships could influence parasite fitness or even increase the likelihood of transmitting pathogens between populations of different bat species.